Slope-Reducing Anterior Closing Wedge Proximal Tibial Osteotomy, Anterior Cruciate Ligament Tunnel Bone Grafting, and Unstable Medial Meniscus Ramp Repair as a First-Stage Procedure - Evan P. Shoemaker, B.A.; Luke V. Tollefson, B.S.; Matthew T. Rasmussen, M.D.; Dustin R. Lee, M.D.; Robert F. LaPrade, M.D., Ph.D. (Arthroscopy Techniques)
Revision anterior cruciate ligament reconstruction (ACLR) requires heightened levels of preoperative patient planning to evaluate for known risk factors of a primary ACLR graft failure. Risk factors include ≥12° of posterior tibial slope, coronal malalignment, nonanatomic femoral or tibial ACLR tunnel placement, and unaddressed ligament/meniscal injury. This technique describes an anterior closing wedge proximal tibial osteotomy, medial meniscus ramp repair, and bone grafting of the failed ACLR femoral and tibial tunnels. This is the first stage of a 2-stage revision ACLR aimed to address an increased posterior tibial slope that contributes to ACLR graft failure while concurrently bone grafting malpositioned failed ACLR tunnels and repairing an unstable medial meniscal tear to prevent further injury or exacerbation before the second-stage procedure.